Avaliação do polissacarídeo da goma do cajueiro (Annacardium occidentale L.) como agente mucoadesivo e controlador da liberação em comprimidos matriciais - Oliveira, Aline Carlos de (2016)
Matricial tablets containing cashew gum polysaccharide (PGC) have been developed in order to promote mucoadhesion and prolonged release of model drugs with different water solubilities (theophylline and ketoprofen). Tablets were prepared by mixing the drug (40% m/m), diluent and PGC (10 to 50%, m/m). The control formulations were prepared by adding diluent instead polysaccharide. Tablets were prepared in a hydraulic press with 12.5 kN compaction force and 10s dwell time. Then, tablets were evaluated for their mechanical properties, drug content, drug in vitro release and mucoadhesive properties. The friability of the tablets met the limits recommended by the Brazilian Pharmacopoeia. The addition of the polysaccharide in the formulation significantly reduced the tablet hardness, which was also affected by the type of drug incorporated. The in vitro release test was carried out in acid medium (2h), followed by 0.4 M phosphate buffer pH 6.8 (6h). A more prolonged profile was achieved in ketoprofen-loaded tablets. In the case of theophylline-loaded tablets, prolonged release was less effective, even when the highest PGC concentration was used (50%, w/w). Ketoprofen-loaded tablets prepared with 30% of PGC released only 9% of the drug in acidic medium. In phosphate buffer, PGC tablets were capable to prolong ketoprofen release. Linearization of the drug release data showed that PGC tablets best fitted the Higuchi model. Mucoadhesion tests showed that the presence of polyssacharide increase tablet adhesion on the bowel membrane. The degree of mucoadhesion was dependent of the PGC concentration, it was greater when 30% (w/w) polysaccharide was added. The results suggests the use of cashew gum polysaccharide in matrix tablets for prolonged release of water-insoluble drugs and as mucoadhesive agent.